ANALISIS PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DI KABUPATEN DAIRI SUMATERA UTARA - Ulina Sihotang, Sarma; Larasati Setianingsih, Endang; Lituhayu, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Population administration services involve the management and regulation of population information within a country through data collection and civil registration activities. These services aim to provide data relevant to public interests, development, and government affairs. The Population and Civil Registration Service in Dairi Regency is a governmental organization responsible for administering population services at the regional level. This research seeks to analyze service delivery and identify obstacles faced in providing population administration services at the Dairi Regency Population and Civil Registration Service in North Sumatra. The research employs a descriptive qualitative approach, utilizing data collection methods such as observation, interviews, documentation, and literature review. The analysis utilizes the Servqual theory by Valerie A. Zeithaml, which encompasses tangible, reliability, responsiveness, assurance, and empathy dimensions. The findings indicate that population administration services at the Dairi Regency Population and Civil Registration Service generally meet the standards outlined in the Decree (SK) of the Dairi Regency Population and Civil Registration Head Number 011 of 2022. However, challenges persist, particularly in achieving the goal of efficient online services due to low utilization rates of applications by the majority of the population. Moreover, offline services suffer from inadequacies such as insufficient waiting room space and form-filling facilities. Recommendations include intensifying socialization efforts across all societal levels, especially regarding online services, enhancing public awareness of the Jempol (jemput bola) program in Dairi Regency, and implementing rigorous monitoring and supervision of all personnel, particularly those at the TPDK, to ensure continued service quality.